Formulation, optimization, and characterization of rifampicin-loaded solid lipid nanoparticles for the treatment of tuberculosis. (2nd December 2018) - Chokshi, Nimitt V.; Khatri, Hiren N.; Patel, Mayur M.
Abstract: Mycobacterium tuberculosis, being the causative infectious agent, is the leading cause of death worldwide amongst the infectious disease. The low bioavailability of rifampicin (RIF), one of the vital constituent of antitubercular therapy, instigates an urge to develop nanocarrier, which can prevent its degradation in the acidic pH of the stomach. Solid lipid nanoparticles (SLNs) have been proven to be promising versatile platform for oral delivery of lipophilic drugs. Therefore, the current investigation demonstrates development of RIF-loaded solid lipid nanoparticles (RIF-SLNs) using high-pressure homogenization technique by employing a three-level, three-factor Box–Behnken design. Concentration of drug, concentration of emulsifier, and homogenization pressure were selected as an independent variables, and %drug loading (%DL), %entrapment efficiency (%EE), and particle size were selected as dependent variables. The developed RIF-SLNs were characterized for particle size, polydispersity index, zeta potential, %EE, %DL, differential scanning calorimetry, X-ray diffraction, and TEM analysis. The mean diameter of RIF-SLNs was found to be 456 ± 11 nm, %EE of 84.12 ± 2.78%, and %DL of 15.68 ± 1.52%. The in vitro lipolysis experiments revealed that RIF-SLNs stabilized using poloxamer 188, exhibited antilipolytic effect. Furthermore, the in vitro GI stability studies (at pH 1.2, pH 4.5, pH 6.8, and pH 7.4) revealed that the developed system could withstand various gastrointestinal tract media. The in vitro dissolution studies depicted biphasic drug release profile for drug-loaded SLNs revealing best fit with Weibull model. The accelerated stability studies for 6 months does not revealed any significant change in characteristics of developed RIF-SLNs.